Trends Research On Local Wisdom In History Learning: A Bibliometric Analysis - Eka Yuliana Rahman; Aldegonda E. Pelealu; Hetreda Terry; Yohanes Burdam; Max Tamon; Meity Najoan; Meike Imbar; Aksilas Dasfordate; Almen S. Ramaino (Technium Social Sciences Journal, 2023)
This paper aims to provide a detailed overview of how to use a bibliometric approach to study local wisdom research trends in history learning. This study is derived from 993 research collections of local wisdom in history learning taken from google scholar data base. We used VOSviewer for bibliometric analysis. Research on local wisdom is very diverse in history learning, and local wisdom in each region provides uniqueness in history learning. Local wisdom in experiments by connecting history learning makes learning diverse. Therefore, based on the results of this bibliometric analysis, it provides an overview and opportunities to conduct future research both quantitatively and qualitatively.